2005
DOI: 10.1532/ijh97.05086
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Trial of High-Dose Chemotherapy Followed by Infusions of Peripheral Blood Stem Cells and Dose-Escalated Donor Lymphocytes for Relapsed Leukemia after Allogeneic Stem Cell Transplantation

Abstract: To determine whether induction of graft-versus-host disease (GVHD) improves the outcome of acute relapsed leukemia after stem cell transplantation (SCT), we used high-dose cytarabine (ara-C) followed by infusions of donor-derived buffy coats containing peripheral blood stem cells to treat 12 patients with relapsed leukemia. Donor lymphocyte infusion (DLI) was repeated at least twice over a 5-week interval for patients in whom grade II to IV acute GVHD did not develop after the first DLI. Grade II to IV acute G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…In addition, several of the relapses presented at unusual extramedullary sites, a phenomenon described before in conjunction with DLI. [35][36][37][38][39] Together, these observations are compatible with the notion that immune intervention may have influenced the timing and presentation of leukemia recurrence. Strong indications for the presence of immunological pressure on leukemic AML cells by the emergence of HLA loss variants have been recently reported.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, several of the relapses presented at unusual extramedullary sites, a phenomenon described before in conjunction with DLI. [35][36][37][38][39] Together, these observations are compatible with the notion that immune intervention may have influenced the timing and presentation of leukemia recurrence. Strong indications for the presence of immunological pressure on leukemic AML cells by the emergence of HLA loss variants have been recently reported.…”
Section: Discussionsupporting
confidence: 68%
“…T-cell-mediated immunotherapy using unmanipulated donor lymphocyte infusion for the treatment of leukemia recurrence in hematopoietic stem cell transplant recipients has had some success in AML, but the use of donor lymphocyte infusion carries a significant risk of inducing graft-versus-host disease. 3 Cytokineinduced killer (CIK) cells are T lymphocytes enriched in CD3 + CD56 + cells, 4 which can be easily and rapidly expanded in vitro from human peripheral blood, bone marrow or cord blood mononuclear cells 5,6 with the sequential addition of interferon (IFN)-g, OKT-3 and high doses of interleukin (IL)-2. 7,8 It has been demonstrated that CIK cells can lyse a broad array of tumor targets in a non-MHC-restricted manner, 4 have the capacity to migrate toward tumor sites 9,10 and display anti-tumor activity in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…3 Moreover, a high incidence of EM relapse following a combination of chemotherapy and donor lymphocyte infusion (DLI) as a treatment for BM relapse also suggests a reduced effectiveness of the GVL effect in EM sites. 5,6 An HLA disparity between donors and recipients is known to elicit a potent GVL effect. [7][8][9] Although a high incidence of severe GVHD has been recognized as a major obstacle to unmanipulated HLA-haploidentical SCT (haplo-SCT), 7 several recent studies have suggested that a potent GVL effect can be successfully maintained in the absence of severe GVHD with some modifications to the immunosuppression protocol [10][11][12] or with the use of G-CSF-mobilized BM cells and PBSCs.…”
Section: Introductionmentioning
confidence: 99%